2022
DOI: 10.1021/acs.joc.2c00841
|View full text |Cite
|
Sign up to set email alerts
|

Development of Biocompatible Ene-Ligation Enabled by Prenyl-Based β-Caryophyllene with Triazoline/Selectfluor under Physiological Conditions

Abstract: Here, we first report a rapid and highly selective biocompatible ligation that proceeds via a strain-promoted prenyl-involved [2, 3]-Ene rearrangement process. We demonstrate the usefulness of naturally occurring strain-promoted β-caryophyllene with triazoline (PTAD)/Selectfluor in the study of tagging molecule-of-interest. Experiments in peptide (Histone H3 (1–21) and Myhc (614–629)) and protein (BSA, βLG, and HSP40) models exemplified the utility of the Ene-ligation for in vivo imaging and tracking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…In addition, we also demonstrated that electron-donating groups on PTAD accelerated the process in a superfast manner. 23 Further stability tests showed that both PTAD-labeling reagents and the resulting coupling adduct are relatively inert to the external environment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we also demonstrated that electron-donating groups on PTAD accelerated the process in a superfast manner. 23 Further stability tests showed that both PTAD-labeling reagents and the resulting coupling adduct are relatively inert to the external environment.…”
Section: Resultsmentioning
confidence: 99%
“…1C and 1D) for the fluorescence labeling and detection of prenyl modified RNAs via a σ-rearrangement mechanism. [23][24][25][26] We also investigated the chemical transformation of the prenyl group in reacting with iodine and utilized this iodinemediated oxidation and reverse transcription (IMORT) approach to profile the i 6 A residues in cellular RNA with a single-base resolution (Fig. 1E).…”
Section: Introductionmentioning
confidence: 99%
“…Next, the dual fluorescent labeling of the target protein lysozyme with citronellol, as well as HRAS and KRAS, has also been evaluated via NEL (SI Figures S17−19) and SACR approaches (SI Figures S20 −21). With respect to citronellolmodified lysozymes, the dual fluorescent labelings with the 1-NO pyrene (2t, 50 μM) targeting lysine residue as well as the PTAD-DBCO-Cy5 (50 μM) 31 targeting tyrosine residue have been carried out simultaneously. It turned out that the in-gel blue fluorescence, red fluorescence, as well as merged pink fluorescence have been determined.…”
Section: Explorations Of the Reaction On Proteinsmentioning
confidence: 99%
“…For instance, the use of IEDDA reaction has been limited in living cells due to the fact that thiol groups in cysteines of many proteins may also react with the coupling reagent trans -cyclooctene (TCO) . Our research group has been interested in lipid modifications on nucleic acids in the past decade. Toward the labeling, sequencing, and manipulation of these unique and important natural RNA modifications, we have developed the ene-ligation method by taking advantage of the reactivity between naturally occurring and strain-promoted β-caryophyllene (βCP) and 4-phenyl-1,2,4-triazoline-3,5-dione (PTAD) . The reaction displays a great potential in biocompatible ligation with high efficiency and selectivity, showing a kinetic of 1.0 mol –1 ·s –1 , which advances over the classic strain-promoted azide–alkyne click chemistry reaction.…”
Section: Introductionmentioning
confidence: 99%